Low Mass Ratio Contact Binary V410 Aur and V776 Cas - II - Kyu-Dong Oh; Chun-Hwey Kim; Ho-iL Kim (Journal of Astronomy and Space Sciences, 2005)
New BVR CCD light curves of the low mass ratio contact binaries, V410 Aur and V776 Cas, were observed with the 61 cm reflector and a 2K CCD camera at the Sobaeksan Astronomical Observatory. The absolute dimensions of the low mass ratio contact binaries, V410 Aur and V776 Cas, were obtained using WD program from the published spectroscopic and newly observed photometric data. The evolutionary status of this type of binary system including V410 Aur and V776 Cas has been considered. We reconfirmed that the primary stars of the low mass contact binary system were located on the TAMS and secondary stars were located under the ZAMS in H-R diagram.